Review of solar photovoltaic/thermal (PV/T) air collector - Ahmad Fudholi; Mariyam Fazleena Musthafa; Abrar Ridwan; Rado Yendra; Hartono Hartono; Ari Pani Desvina; Majid Khan Bin Majahar Ali; Kamaruzzaman Sopian (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Growing concern with regard to energy sources and their usage has consequently increased significance of photovoltaic thermal (PV/T) collectors. A PV/T air collector is a system which has a conventional PV system combined with a thermal collector system. The system is able to produce electrical energy directly converted from sunlight by using photoelectric effect. Meanwhile, it also extracts heat from the PV and warms the fluid (air flow) inside the collector. In this review, solar PV system and solar thermal collectors are presented. In addition, studies conducted on solar PV/T air collectors are reviewed. The development of PV/T air collectors is a very promising area of research. PV/T air collectors using in solar drying and solar air heater.